The Impact of Open Data Implementation on Entrepreneurial Attitude with Regard to Moving towards UN Sustainability Goals - Ekundayo, Tosin; Bhaumik, Amiya; Chinoperekweyi, Justine; Khan, Zafarullah (Foresight and STI Governance, 2023)
This study aimed to investigate the impact of open data implementation as part of its data governance initiatives on entrepreneurial attitudes in Europe and Central Asia. The impact of open data implementation in transforming entrepreneurial attitudes in Europe and Central Asia has never been determined or investigated in a measurable form. Using regression (OLS) analysis of secondary data on the open data implementation index from the Open Data Barometer (ODB) and the Entrepreneurial Attitude index from GEI, this study investigates the impact of open data implementation (as a national data governance strategy) on entrepreneurial attitudes in Europe and Central Asia. This study introduces a novel approach by integrating open data implementation into the analysis of entrepreneurial attitudes, a perspective yet to be explored in the context of Europe and Central Asia, thereby advancing our understanding of sustainable development goals. The study establishes a causation of the 32% impact of open data implementation on entrepreneurship attitudes toward recognizing opportunities in Europe and Central Asia. This study advocates for the establishment of a comprehensive national open data initiative as a catalyst for fostering entrepreneurial attitudes within Europe and Central Asia. Moreover, it emphasizes the importance for entrepreneurs to cultivate the necessary attitude for achieving their business objectives successfully. The study recommends further investigation using a recent dataset. The study’s findings improve the understanding of how to induce entrepreneurship attitudes in Europe and Central Asia in pursuit of post-pandemic economic development.